A computational model for evaluating the efficiency of multi-frequency digital radio systems - Victor P. Tsvetov; Alexei V. Grafkin; Alexandr S. Lukanov (Физика волновых процессов и радиотехнические системы)
Background. Frequency division multiplexing scheme is a promising technology for wideband digital communication. Systems like this have significantly increased the speed of wireless data transmission, including in complicated conditions of multipath propagation of a radio signal. The first step in designing radio equipment is to evaluate its effectiveness in terms of the use of allocated resources. Aim. The paper describes a mathematical model of multi-frequency digital radio systems and the architecture of a software and hardware platform designed to study the information and energy efficiency of these systems. Methods. The mathematical model is based on the Hilbert spaces and information theory. Its numerical implementation makes it possible to take into account the entropy of message sources, the spectral characteristics of the signal and interference, the signal-to-noise ratio, etc. Results. The paper presents the results of numerical experiments comparing the efficiency of radio communication systems based on frequency division multiplexing and quadrature amplitude modulation schemas, and shows the capabilities of the designed software and hardware platform. Conclusion. The constructed model for evaluating the effectiveness of multi-frequency digital radio communication systems and its implementation make it possible to automate the process of analyzing the characteristics of wireless communication systems.